Community Based Self-Administered Syndromic Surveillance Mobile Application - A Strategic Approach to Monitor COVID Situation at Micro Level - K A Narayan; M Siva Durga Prasad Nayak (Medsci Publications, 2020)
Introduction: Web based surveys avoid direct contact of health care workers to collect information and protect them from harmful exposure to the infectious diseases. They have already been used for influenza in different countries. Success of any health program depends upon the community participation, in a similar way participatory surveillance activity will help healthcare administrators work in early detection of cases and initiation of early treatment. Methodology: Glide apps is a free platform to create mobile applications using Google spreadsheets. Creation and sharing of mobile app in Glide apps platform is hassle-free work and needs only a Gmail account. Based on this background, a mobile application was developed using Glide apps platform to collect information at micro level, about development of COVID symptoms in the public. Results: The article discussed about need of community participation in the surveillance program and development of web based self-administered surveillance tools. Steps in creation of the mobile application were explained in detail and features of the surveillance tool were also depicted with images. Conclusion: The advantages of participatory surveillance system over traditional surveillance practice were mentioned. Traditional surveillance system collects information through health care workers, whereas in participatory surveillance program information will come from the public. Strengths and limitations of the surveillance tool were discussed and scope for further development of the mobile application was also mentioned in the current review article.